Clinical trial data transparency and GDPR compliance: Implications for data sharing and open innovation. (4th March 2020) - Minssen, Timo; Rajam, Neethu; Bogers, Marcel
Abstract: Recent European Union (EU) initiatives and legislation have considerably increased public access to clinical trials data (CTD). These developments are generally much welcomed for the enhancement of science, trust, and open innovation. However, they also raise many questions and concerns, not least at the interface between CTD transparency and other areas of evolving EU law on the protection of trade secrets, IPRs, and privacy. This article focuses on privacy issues and on the interrelation between developments in transparency and the EU's new General Data Protection Regulation 2016/679 (GDPR). More specifically, this article examines: (1) the origins and rationales of EU transparency regulations, including the incidents and concerns that have shaped them; (2) the features and implications of the GDPR which are relevant in the context of clinical trials; and (3) the risk for tensions between the GDPR and the policy goals of CTD transparency, as well as implications for data sharing and open innovation. Ultimately, we elaborate on factors that should be carefully considered and addressed to reap the full benefits of CTD transparency.